1993
DOI: 10.3109/03009749309095105
|View full text |Cite
|
Sign up to set email alerts
|

Grip Force in Patients with Rheumatoid Arthritis and Fibromyalgia and in Healthy Subjects. A Study with the Grippit Instrument

Abstract: The reliability of the grip force instrument, Grippit was tested on 51 right-handed women of which 18 were healthy, 19 had rheumatoid arthritis (RA) and 14 had fibromyalgia (FM). Normative data was obtained from 169 healthy subjects. Results indicate that the reliability of Grippit was high in healthy and rheumatoid arthritic women and satisfactory in women with fibromyalgia. All patients showed greatly reduced grip force (RA had on average 21% and FM 40% of the control values) when compared to healthy women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
239
6

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(263 citation statements)
references
References 14 publications
18
239
6
Order By: Relevance
“…Previous studies support this model by demonstrating decreased muscle strength associated with pain. Reduced grip strength (34), sustained pain on jaw closing (35), and reduced bite strength (36) have been reported in patients with pain. The reduction in muscle force exertion associated with TMJ disorders may result from decreased activity of agonist muscles and increased activity of antagonist muscles (37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies support this model by demonstrating decreased muscle strength associated with pain. Reduced grip strength (34), sustained pain on jaw closing (35), and reduced bite strength (36) have been reported in patients with pain. The reduction in muscle force exertion associated with TMJ disorders may result from decreased activity of agonist muscles and increased activity of antagonist muscles (37).…”
Section: Discussionmentioning
confidence: 99%
“…The Borg CR-10 scale ranges from 0 (no pain) to 10 (very severe pain) (37). Grip strength was evaluated using the Grippit, which is an electronic force instrument measuring both maximum force and mean force in newtons over a 10-second period (38).…”
Section: Assessments Of Impairmentmentioning
confidence: 99%
“…Of the 59 patients who dropped out and did not complete the EDAQ, 37 were women (median age 50 years, IQR 27 at inclusion) and 22 were men (median age 59 years, IQR 23 at inclusion). Age, erythrocyte sedimentation rate (ESR), plasma C-reactive protein (CRP), DAS28 (28), grip force (21), and HAQ score (29) did not differ between the study group and the dropouts, whereas the dropouts reported significantly more general pain on a 0 -100-mm visual analog scale (VAS) (P ϭ 0.023) and more tender joints (P ϭ 0.04).…”
Section: Introductionmentioning
confidence: 99%
“…Maximum, momentary, and average grip force (N) over a period of 10 seconds were measured in the right and the left hand separately using a digital electronic device (Grippit; Detektor AB, Gö teborg, Sweden) (21). In this study, the average grip force of 10 seconds in the right hand was used.…”
Section: Introductionmentioning
confidence: 99%